Increase in precipitation and fractional vegetation cover promote synergy of ecosystem services in China’s arid regions—Northern sand-stabilization belt - Wei, Changwen; Su, Kai; Jiang, Xuebing; You, Yongfa; Zhou, Xiangbei; Yu, Zhu; Chen, Zhongchao; Liao, Zhihong; Zhang, Yiming; Wang, Luying (Frontiers in Ecology and Evolution, 2023)
Research on synergies and trade-offs between ecosystem services (ES) contributes to a better understanding of the linkages between ecosystem functions. Relevant research mainly focuses on mountain areas, while research in arid areas is obviously insufficient. In this research, we use the northern sand-stabilization belt (NSB) as an example to explore how the synergies and trade-offs between different ES vary with the gradient of precipitation and fractional vegetation cover (FVC) over the period 2000-2020. Based on five simulated ecosystem services (habitat provision, sand-stabilization service, water conservation service, soil conservation service and carbon sequestration service), the Pearson correlation coefficient method was used to analyze the various characteristics of the trade-offs and synergies among the different ES pairs along the FVC and precipitation gradients. Results showed that: Synergies between most paired ES increased significantly with increasing precipitation and FVC. However, ES have different sensitivities to environmental change, FVC promotes bit more synergy of ES pairs than precipitation. The study also found that land use/land cover may be an important driving factor for trade-offs and synergies between paired ES. The findings demonstrate that increased precipitation and FVC promote synergy of ecosystem services in arid regions of China. In the future, it can be investigated whether anthropogenic increase in FVC in arid regions can significantly contribute to the synergy of ES. In the meantime, this study could improve our understanding of arid and semi-arid (or macro-regional) ecosystems and contribute to the development of ecosystem management and conservation measures in NSB.